2020
DOI: 10.32604/phyton.2020.07665
|View full text |Cite
|
Sign up to set email alerts
|

Safflower (Carthamus Tinctorius L.) a Potential Source of Drugs against Cryptococcal Infections, Malaria and Leishmaniasis

Abstract: In this research we present that Carthamus Tinctorius L. (gen. Asteraceae, otherwise known as Safflower) (Fig. 1) may contain agents active in Cryptococcal infections, malaria and Leishmaniasis, as treatment options are becoming scarce due to drug resistance development. Phytochemistry and pharmacological activities (antimicrobial, antimalarial, antileishmanial) of C. tinctorius L. were analyzed. The composition of volatile oil of safflower dried flowers was analyzed by gas chromatography-mass spectrophotometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Regarding the properties and applications of the major components, EOs containing high levels of ( Z )-α-trans-bergamotene may have antibacterial and antifungal activities [ 86 , 87 ]. This compound is also used in industry as a flavoring agent and can be found in the aromas of cereals and other derivatives [ 88 ]. α-Sinensal is responsible for the sapodilla aroma and is also used in the food, cosmetics, and perfumery industries as a flavoring because it has an intense orange aroma accompanied by distinct floral notes [ 89 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the properties and applications of the major components, EOs containing high levels of ( Z )-α-trans-bergamotene may have antibacterial and antifungal activities [ 86 , 87 ]. This compound is also used in industry as a flavoring agent and can be found in the aromas of cereals and other derivatives [ 88 ]. α-Sinensal is responsible for the sapodilla aroma and is also used in the food, cosmetics, and perfumery industries as a flavoring because it has an intense orange aroma accompanied by distinct floral notes [ 89 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, plant extract use with antifungal power is a promising alternative against these diseases [ 23 ]. Previous studies have shown that the safflower water extract has antibacterial properties against various bacteria such as Bacillus subtilis , Bacillus cereus , and Bacillus mycoides [ 24 ]. Another study showed that safflower methanolic and water extracts have a high potency in inhibiting the growth of S. aureus , E. coli , P. aeruginosa , and K. pneumonia bacteria and their inhibitory power varies depending on the type of bacteria [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there are some obstacles hindering the internationalization of TCM. As a distinctive feature, the multiple parts of plants, such as roots [4], leaves [5], flowers [6], and seeds [7], etc., can be used as a source for TCM. Generally, herbal medicines contain various chemical components, which are featured by the co-existance of primary and secondary metabolites with wide spans of acidity-base properties and molecular masses, different polarities, and sharply different contents, etc.…”
Section: Introductionmentioning
confidence: 99%